Pelestarian Tari Ambek-Ambek Oleh Sanggar Timbulun Koto Basaga Di Nagari Koto Anau Kecamatan Lembang Jaya Kabupaten Solok - Rizka Gasima Putri; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2021)
This study aims to determine the preservation of Ambek-ambek dance by SanggarTimbulun Koto Basaga in Koto Anau village, Lembang Jaya District, Solok Regency. This research belongs to a qualitative research using a descriptive method. The object of this research wasAmbek-ambek dance by Sanggar Timbulun Koto Basaga in Koto Anau village, Lembang Jaya District, Solok Regency. The main research instrument in this study was the researcher itself. The tools used in the research were writing instruments, photo cameras, and flash drives. The data were collected through literature studies, observation, interview, and documentation. Ambek-ambek dance tells about a woman who was sewing. Then a man arrived to draw her attention so they joke together. The results show that Ambek-ambek dance is preserved through protection, development, and utilization. Protection is carried out by holding dance training every two times a week, development is carried out by developing the costume section but it still sticks to traditional values, and utilization is carried out by performing dance at school events, alek nagari, competition events, and wedding parties. Thus, Ambek-ambek dance is known by all groups both local and outside the city.